Factors that affect Fraud Detection: Internal Auditor Independence and Whistleblowing System - Raisah Nur Hotimah; Cris Kuntadi (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2024)
Previous research or relevant research plays a crucial role in building theoretical foundations and hypotheses for future research. This article aims to review the factors that influence fraud detection, focusing on internal auditor independence and whistleblowing system. Internal auditor independence reflects the ability of auditors to perform their duties objectively and unaffected by internal organizational interests, while the whistleblowing system provides a secure communication channel for organizational members to report fraud without fear of reprisal. With a deepened understanding through this article, it is expected to generate strong hypotheses about the relationship between these factors in the context of fraud detection, which can help improve the effectiveness of fraud prevention and detection efforts in various sectors and organizations. The results of this literature review article are: 1) Internal Auditor Independence affects Fraud Detection and 2) Whistleblowing System affects Fraud Detection.